NESTING BEHAVIOR OF THE ANDEAN HUMMINGBIRD (AMAZILIA FRANCIAE BOURCIER & MULSANT, 1846) AND THE ECOSYSTEM SERVICES IT PROVIDES IN THE PEASANT COMMUNITY OF YANANYAC, HUANCAVELICA, PERU - Jaime-Huaman, Emerson (2022)
The objective of this work was to describe the nesting behavior of the Andean hummingbird (Amazilia franciae Bourcier & Mulsant, 1846) and to classify the ecosystem services it provides in the peasant community of Yananyac, Huancavelica, Peru according to the evaluation of the Millennium Ecosystems of the United Nations. Monitoring of ten Andean hummingbird nests was carried out in the months of April and May 2021 in an agricultural area of ​​the peasant community of Yananyac. The nests were located between bushes and fruit-bearing plants, at an average height of 1.84 m. The nests were made with a base of dry leaves, cobwebs, lichens, feathers, flower stamens and seeds; covered with fibers, built mainly with the scales and trichomes of ferns, with an average depth of 18.4 mm. The eggs are white and oval in shape, measuring 7.44 mm wide and 12.3 mm long. The chicks presented different times of growth and development. The services provided by the Andean hummingbird according to the United Nations Millennium Ecosystem Assessment are regulation, support, provisioning and culture. The first being the most important due to the role that this species plays in the pollination of crops in the peasant community of Yananyac.